Answer:
1663 m approx.
Step-by-step explanation:
We have a right triangle in which we know the hypotenuse and need to find the opposite side, so we use the sine function:
sin 12 = h / 8000
h = 8000 sin 12
= 1663 m approx.
Answer:
4/5
Step-by-step explanation:
{(2/5) / (1/2)} ×1
= (2/5)÷(1/2)
= 2/5×2/1
= 4/5
Answer:
4/5
Step-by-step explanation:
Because if it can eat 2/5's in 1/2 hours, then if it eats for 1 whole hour or 2/2's it will be able to eat 4/5's of it's own body weight.
Just imagine that one half hour is 1 and if you add two half hours together it makes one complete hour or 2/2. So just multiply it by 2 cause it was eating for two half hours.
Therefore, the factors of 15 are 1, 3, 5, and 15. The number 15 has more than two components, making it a composite number.
A number that equally divides into a number is referred to as a factor, to give a more thorough explanation.
A factor of 15, for instance, is 3 since 15 / 3 equals 5. A number with precisely two elements, 1 and itself, is said to be a prime number. For instance, the only integers that divide evenly into 2 are 1 and 2, making 2 a prime number.
A number with more than two elements is said to be composite. For instance, 15 is a composite number since 1, 3, and 15 are all divided evenly into 15.
Therefore, 1, 3, 5, and 15 are the factors of 15. 15 has more than two components, making it a composite number.
More about the composite number link is given below.
#SPJ6
5x – 2.5y = 5
What equation is the result of adding the two equations?
What is the solution to the system?
Answer:
x=4 Y=6
Step-by-step explanation:
For the function f defined by f(x) = 2x^2 – 3x, evaluate: f(x+3)
Answer:
2x² + 9x + 9
Step-by-step explanation:
To evaluate f(x + 3) substitute x = x + 3 into f(x), that is
f(x + 3) = 2(x + 3)² - 3(x + 3) ← expand (x + 3)² using FOIL
= 2(x² + 6x + 9) - 3(x + 3) ← distribute both parenthesis
= 2x² + 12x + 18 - 3x - 9 ← collect like terms
= 2x² + 9x + 9
B )y+5=1/3(x+9)
C) y-5=3(x-9)
D) y-5=1/3(x-9)
Answer:
y=x-5
Step-by-step explanation:
First, you find the slope by -2-(-5)/3-0. This would be 3/3 which is equal to 1. Then you plug in the x with any point you want. I'm going to use (3,-2). The equation should look like -2=3+y. Now we find what is y. Therefore for this equation to be true. Y is equal to -5. Now put it all together. Y=x-5. You can use the other point to check my answer! Hope that helps!!